Penggunaan Teknik Modeling Simbolik Untuk Meningkatkan Kepercayaan Diri Siswa Tunagrahita Ringan Kelas VIII Di SLB Negeri 1 Bulukumba - Nuraidah; Abdullah Pandang; Sahril Buchori (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study examines the low self-confidence of mildly disabled students at SLB Negeri 1 Bulukumba. The formulation of the problems in this study are (1) What is the description of the behavior of self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba based on the analysis of the initial condition/baseline 1 (A1); (2) How is the description of the implementation of modeling techniques in increasing the self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba in the intervention condition (B); (3) Whether modeling techniques can increase the self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba based on the results of the analysis of the final condition of baseline 2 (A2).